QUALIDADE DE VIDA NO TRABALHO E O COMPROMETIMENTO COM A CARREIRA: A PERCEPÇÃO DOS DIRETORES DE ESCOLAS DA REDE PÚBLICA ESTADUAL DO PARANÁ - ANDRADE, LUCIANA BORTONCELLO LORENZETTI (2017)
This dissertation presents the quality of work life and the commitment to the career as its theme for the Post-Graduate Program in Administration, of the Professional Master in Administration of the State University of the Central West (UNICENTRO – Portuguese abbreviation). The research approaches the subject with strategy research line, considering that the quality of work life and the commitment to the career are relevant aspects for the employees and the organizations in which they work, may they be public or private. The purpose of this study was to analyze the level of satisfaction regarding factors affecting quality of work life and the relationship with the commitment to the career, in the perception of 410 teachers who act as school directors of the Public Education System of Paraná State. It is a descriptive, cross-sectional study with quantitative approach and survey. The data were collected from October to December 2016 through an research instrument made up of: Questionnaire adapted from the Biopsychosocial and Organizational Analysis Model -BPSO- 96 of Quality of Life at Work, Questionnaire of the Scale of Commitment to the Career and Questionnaire on the socioeconomic profile of the director. The quantitative data were statistically treated using specific software such as the Excel® for the initial data tabulation; for the information analysis, the Statistical Package for the Social Science (SPSS) was adopted. Normality, parametric (average and standard deviation), Cronbach's Alpha coefficient reliability and Pearson's correlation tests, as well as comparative analysis between socioeconomic data and study variables were performed. It was identified that most of the directors who participated in the research are female, married, between 46 and 52 years old, that have been teaching for more than 20 years and that are in the direction of the school for 2 years, on average. They work in the morning and afternoon periods and have full specialization in School Administration or in other areas. The results showed that in the rate representation, the different organizational, biological, psychological and social domains reflect in the director's perception of dissatisfaction and neutrality (neither satisfied nor dissatisfied). The psychological domain had the highest average of 3,38 and the biological domain received the lowest one (2,59), presenting the highest dissatisfaction level than the other variables. The averages found in the variables of commitment to the career are in compliance with existing literature, exhibiting a smaller variation for Cronbach's Alpha regarding identity and career planning. Pearson's (r) analysis indicate the existence of a weak intensity correlation between the QLW and the factors in the commitment with the carrer. Cluster´s analysis identified the formation of significative grouping either to QLW as to the commitment with the carrer. The T Test and ANOVA (Portuguese abbreviation) indicate the differences among the QLW domains, the commitment factors with the carrer and the principals’ socioeconomic profile. The results demonstrated that the teachers in the State of Parana, in public school principal function, are dissatisfied in relation to QLW, indicating a major dissatisfaction in relation to the health aspects, finding themselves however, identified to their teaching carrers.